Epidemiology and traumatology of injuries in elite soccer: a prospective study in Finland - Luthje, P.; Nurmi, I.; Kataja, M.; Belt, E.; Helenius, P.; Kaukonen, J. P.; Kiviluoto, H.; Kokko, E.; Lehtipuu, T. P.; Lehtonen, A.; Liukkonen, T.; Myllyniemi, J.; et al. (Scandinavian Journal of Medicine & Science in Sports, 1996)
A prospective study of male soccer injuries among 12 teams playing at the highest competition level was carried out in Finland in 1993. Overall, two out of three players were injured during the whole season. The injury incidence per 1000 playing hours among injured players and all players during games was higher than during practice, 14.2 vs. 11.3 and 2.3 vs. 1.8, respectively. The lower extremity was involved in 76% of the injuries. Thigh injuries were most frequent (22%), whereas overuse injuries were scarce (6%). Eighteen per cent of the injured players needed surgery and in most cases (58%) the reason for surgery was a knee injury. Sixteen per cent of all injured players were absent from soccer for more than 1 month after the injury. The mean absence time was 17 days for all and 84 days for operatively treated players. Scand J Med Sci Sports 1996 Jun;6(3):180-5